Business Schools, Leadership and Sustainable Development Goals : The Future of Responsible Management Education - Moratis, L. T., (Lars T.), editor 650015; Melissen, Frans, editor 650017 (New York, NY : Routledge, 2023)
"Business Schools, Leadership and Sustainable Development Goals: The Future of Responsible Management Education is the second book in the series Citizenship and Sustainability in Organizations: Exploring and Spanning the Boundaries. It contains chapters from various scholars and practitioners in the field of responsible management education (RME). Through introspection, through celebrating successes and learning from failures (retrospection) and through looking forward (prospection), it aims to inspire a future of management education and leadership development that demonstrates its relevance to sustainable development. In doing so, it touches upon the grand societal challenges of our time, as illustrated by the United Nations Sustainable Development Goals, and discusses how business schools, and other providers of management education, could and should contribute to overcoming these challenges. It argues that management education needs to educate future leaders in a way that no longer hampers but truly accelerates the process of sustainable development. This book offers a collection of thought-provoking ideas, vivid stories (including personal accounts and experiences), and appealing and engaged forecasts, visions and ideas about management education and leadership development for sustainability. Hence, it is a must-read for anyone interested in or involved in RME"--